Occupational Stress and Its Effects on Nurses at a Health Facility in Ho Municipality, Ghana - Anita Fafa Dartey PhD, M Nursing, OHNP, RN; Vivian Tackie MPH, BscN, RN; Comfort Worna Lotse Mphil, BPH, RN; Emmanuel Dziwornu PhD, MPhil, BA; Derrick Affrim BNur; Dabi Rejoice Delanyo Akosua BNur (SAGE Publishing, 2023)
Introduction The prevalence of occupational stress among nurses varies significantly around the globe. Nursing is often considered a stressful occupation and can have negative effects on the mental, physical, family relationships, and quality of care given to patients. The aim of this study was to explore the experiences, causes, effects, and coping strategies of occupational stress among nurses working at a health facility in Ho Municipality in Ghana. Methods The study employed a qualitative research approach with an exploratory design. Data saturation was reached with 18 participants. Purposive sampling was used to select participants, while semistructured interview guide with voice recorders were used in data collection. Data were manually transcribed and analyzed using thematic analysis. Results Overall, four main themes and ten subthemes were developed from this study. The main themes were nurses' perception of occupational stress, sources of occupational stress, effects of occupational stress, and coping strategies adopted to cope with occupational stress. The subthemes were as follows: negative and positive stressful feeling, individual level, hospital level, general body pain and fatigue, mental health problems, ineffective relationships, low work output, diversional therapy, positive work outcomes, and psychological support from others (family and colleagues). Discussion There are more negative effects of occupational stress on nurses. However, most of the nurses adopted coping strategies to reduce stress with little or no support from the hospital. More support from the hospital will be required to totally manage occupational stress. Conclusion The study findings revealed how stress affects the daily life and work output of nurses. It is crucial to comprehend how work-related stress affects nurses and what aspects of their workplace are the most burdensome.